1991
DOI: 10.1111/j.1447-0756.1991.tb00260.x
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal Spread and Its Prognostic Impact in Stages I and II (FIGO) Endometrial Carcinoma

Abstract: Prognostic risk factors were statistically analyzed from the histopathologic data obtained from 90 Japanese women with stages I and II endometrial carcinoma treated surgically, including systemic retroperitoneal lymph node dissection, between June 1979 and June 1989. In stage Ia endometrial carcinoma, pelvic and paraaortic nodes metastasis were seen in 13.8(4/29)% and 0.0(0/19)% of patients, respectively. In stage Ib, the incidence of pelvic and paraaortic node metastasis was 25.6(11/43)% and 9.7(3/31)%, respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 26 publications
0
5
0
1
Order By: Relevance
“…Thus, it is reasonable to consider whether the ovaries should be routinely removed and evaluate how high the risk is for residual cancer in preserved ovaries at surgery for early endometrial carcinoma, especially clinical stage I disease. It has been reported that the rate is about 1.7–11% in clinical stage I endometrial carcinoma, 5–9 but the reported results are not consistent. Takeshima et al 9 .…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…Thus, it is reasonable to consider whether the ovaries should be routinely removed and evaluate how high the risk is for residual cancer in preserved ovaries at surgery for early endometrial carcinoma, especially clinical stage I disease. It has been reported that the rate is about 1.7–11% in clinical stage I endometrial carcinoma, 5–9 but the reported results are not consistent. Takeshima et al 9 .…”
Section: Discussionmentioning
confidence: 85%
“…13 Thus, it is reasonable to consider whether the ovaries should be routinely removed and evaluate how high the risk is for residual cancer in preserved ovaries at surgery for early endometrial carcinoma, especially clinical stage I disease. It has been reported that the rate is about 1.7-11% in clinical stage I endometrial carcinoma, [5][6][7][8][9] but the reported results are not consistent. Takeshima et al 9 reported that the rate of ovarian implant was 5% in 439 patients with clinical stage I endometrioid adenocarcinoma, but 4.5% if those with nonendometrioid adenocarcinoma, extrauterine spread other than ovary, and pelvic lymph node metastasis were excluded.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Many pathologic factors have a direct effect on the prognosis (3,7,18,19) , but extrauterine involvement (including lymph node metastasis) is particularly important (20) . In several reports, it was reported that patients with para-aortic lymph node metastasis have a worse prognosis than those who are only positive for pelvic lymph node metastasis (4,10) , and para-aortic lymph node metastasis has also been shown to affect the prognosis (8,(20)(21)(22)(23)(24)(25)(26)(27)(28) . Though such findings suggest that the presence of para-aortic lymph node metastasis is one of the factors worsening the prognosis, the therapeutic meaning of para-aortic lymph node dissection is uncertain.…”
Section: Discussionmentioning
confidence: 99%